1990
DOI: 10.1038/ki.1990.323
|View full text |Cite
|
Sign up to set email alerts
|

ANP inhibits Na+-H+ antiport in proximal tubular brush border membrane: Role of dopamine

Abstract: Infusion of ANP to rats results in an inhibition of Na(+)-H+ antiport and Na(+)-Pi symport in brush border membrane vesicles (BBMV) prepared from kidneys of these animals (J Clin Invest 75:1983). iIn the present study we investigated the intrarenal mechanism by which infused ANP elicits these changes in proximal tubular transport systems. As in rats, infusion of ANP to rabbits resulted in a diuresis, natriuresis, and increase in GFR; however, unlike in rats, the fractional excretion of phosphate (Pi) was not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 24 publications
4
37
1
1
Order By: Relevance
“…Based on previous studies, the chief sites of ANP action were thought to be in glomeruli, IMCD, and CCD (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)24). Although ANP inhibits Na and fluid reabsorption in IMCD and CCD, which can contribute substantially to the natriuresis and diuresis of ANP, the results of micropuncture studies (7,14,33) (6,12,(34)(35)(36). Our present data completely agree with these data.…”
Section: Discussionsupporting
confidence: 81%
“…Based on previous studies, the chief sites of ANP action were thought to be in glomeruli, IMCD, and CCD (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)24). Although ANP inhibits Na and fluid reabsorption in IMCD and CCD, which can contribute substantially to the natriuresis and diuresis of ANP, the results of micropuncture studies (7,14,33) (6,12,(34)(35)(36). Our present data completely agree with these data.…”
Section: Discussionsupporting
confidence: 81%
“…This may have resulted in enhanced renin release due to decreased sodium delivery to the macula densa ( 31 ) and further activation of aldosterone. Indeed, ANP has been demonstrated to reduce proximal tubule sodium reabsorption via a dopamine mediated mechanism (30). In the current study, proximal tubule sodium handling was indirectly determined by lithium clearance, as supported by previous studies which have demonstrated the validity of lithium clearance as an accurate method of estimating whole kidney proximal tubular sodium reabsorption ( 17,18).…”
Section: Discussionsupporting
confidence: 79%
“…The reduction in sodium excretion and the blunted natriuretic response to volume expansion in the ELVD-APPX group are consistent with the effects of ANP to enhance sodium excretion via known renal tubular effects (29,30) and by opposing the antinatriuretic effects of the RAAS. The physiological mechanism responsible for activation of the RAAS and sodium retention in the absence of elevation of ANP can only be speculated.…”
Section: Discussionsupporting
confidence: 68%
“…19 Furthermore, ANP acts within the kidney to increase GFR 6,20,21 and to decrease proximal sodium and water reabsorption via both inhibition of angiotensin-stimulated transport and a dopamine mediated mechanism. 22,23 The administration of HS-142-1 may decrease sodium delivery to macula densa. During continuous infusion of HS-142-1, since PRA changed in proportion to the urinary sodium excretion rate, decreased sodium delivery to the macula densa may enhance renin secretion.…”
Section: Plasma Hormonal Changesmentioning
confidence: 99%